Improving Student Learning Outcomes in History Lessons Through a Jigsaw Type Cooperative Learning Model in CLASS X-2 SMA Negeri 2 Medan - Pudi, Cut Ainun; Sumantri, Pulung; Aisyah, Siti (LPPPI Publishing, 2024)
This research is a type of PTK research, by implementing a jigsaw type cooperative learning model in class X-2 of SMA Negeri 2 Medan, the aim of this research is to improve student learning outcomes. The number of students in class X-2 is 36 students. The subjects in this research were class X-2 students who were part of the population of this study, the population in the study were class This research consisted of 2 classroom action cycles, cycle 1 stated that the class average score was 86.4 which was quite good, however in cycle 1 there were still students who had not yet completed the KKM, namely a score of 75 even though their classical completion exceeded 83%. Then in cycle 2, the data on student learning outcomes obtained an average class learning outcome of 95 which was in the very good category 85%.